The Erratic Implementation of Measuring, Monitoring and Control System (Mmcs) in Chile: The Crisis on Smart Meters - Becker-Cares, C; Verdejo-Fredes, H (Elsevier Ltd, 2020)
The implementation of the Measuring, Monitoring and Control System (MMCS) in Chile was the key element of the most important regulatory and political crisis which has affected the Chilean electric sector. In the news this period was named as “smart-meters crisis”. This crisis was also one of the elements that contributed to the social outburst in October 2019. This paper presents both the technical and regulatory background that explain the failure of a public policy intended to modernize the electric distribution grid. It is described the arguments that promoted the investment of the companies on the MMCS, the antecedents that lead the Government to eliminate the obligations opting for the voluntariness in relation to the change of smart meters during the implementation process and the dilemma generated with regards to the pilot projects developed by some electrical distribution companies. Finally, a solution is proposed for the smart-meter s property dilemma. © 2020 The Author(s)